MELIOLALES FROM INDONESIA - C. G. HANSFORD (REINWARDTIA, 1954)
The present account is based on the representation in Herbarium Bogoriense of the genera Amazonia Theiss., Arviatella Theiss. & Syd.,Irenina P. L. Stev., Irenopsis P. L. Stev., and Meliola Fr., as far as the Indonesian material is concerned. The total number of species is 134, of which 39 species and 12 varieties are described as new, most of which belong to Meliola.